2020
DOI: 10.1093/nar/gkaa334
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide organization of subcellular microenvironments revealed by ATLAS-Seq

Abstract: Subcellular organization of RNAs and proteins is critical for cell function, but we still lack global maps and conceptual frameworks for how these molecules are localized in cells and tissues. Here, we introduce ATLAS-Seq, which generates transcriptomes and proteomes from detergent-free tissue lysates fractionated across a sucrose gradient. Proteomic analysis of fractions confirmed separation of subcellular compartments. Unexpectedly, RNAs tended to co-sediment with other RNAs in similar protein complexes, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Also, mRNAs enriched in nuclear locations tend to code for proteins enriched in nuclear speckles and nucleoplasm. Alternatively, subcellular RNA colocalization can also be detected by AT-LAS-seq, which uses sucrose density gradient ultracentrifugation followed by RNA sequencing (Adekunle and Wang 2020). In this study, it was also found that RNAs tended to colocalize with other RNAs in similar protein complexes, in cellular compartments, or with similar biological functions.…”
Section: Subcellular Structure Analysismentioning
confidence: 59%
“…Also, mRNAs enriched in nuclear locations tend to code for proteins enriched in nuclear speckles and nucleoplasm. Alternatively, subcellular RNA colocalization can also be detected by AT-LAS-seq, which uses sucrose density gradient ultracentrifugation followed by RNA sequencing (Adekunle and Wang 2020). In this study, it was also found that RNAs tended to colocalize with other RNAs in similar protein complexes, in cellular compartments, or with similar biological functions.…”
Section: Subcellular Structure Analysismentioning
confidence: 59%
“…P-bodies, SGs, neuronal granules, and germ granules contain hundreds to thousands of mRNA species [6,8,9,13]. Although no method exists currently to simultaneously purify distinct cellular condensate subtypes and directly characterize their transcriptome, ATLAS-Seq, a novel fractionation method coupled to RNA-sequencing identified hundreds of clusters of RNAs that co-segregate with their regulatory proteins [53], supporting a model where RNAs coassemble into supramolecular assemblies that have not yet been described. Small noncoding RNA (ncRNA) content has not been characterized on a transcriptome-wide scale, but miRNAs are stably anchored and numerous proteins from the Argonaute family collect in condensates [9,[54][55][56][57].…”
Section: The Diversity and Complex Composition Of Endogenous Condensatesmentioning
confidence: 99%
“…Overall, RNA condensation and solubilization within cytosolic condensates, whose diversity reaches far beyond P-bodies and SGs to include a wide array of cell-type-specific condensates, as well as an increasing list of nuclear bodies, provides a powerful mechanism to sort and organize RNA transcriptome-wide (Figure 4). Novel sequencing approaches such as ATLAS-Seq, suggest that hundreds of RNA supramolecular assemblies remain to be elucidated [53].…”
Section: Redundant Alternative Protein Scaffolds Create Robust Super-mentioning
confidence: 99%
“…Localization of proteins is then inferred by comparing their gradient distribution J o u r n a l P r e -p r o o f 10 patterns to those of known organelle marker proteins, usually performed using computational machine learning strategies, such as support vector machine (SVM) classification (Figure 3b) [238][239][240][241] . PCP was originally applied to single compartments of interest, such as the centrosome, peroxisome, lipid droplet, proteasome in various model organisms [242][243][244][245] . The technique was expanded for global organelle analyses in multiple mouse tissues 246,247 .…”
Section: Protein/rna Correlation Profilingmentioning
confidence: 99%